Mythology and Politics: The Myth of the Founding of Vilnius as a Historical Narrative - Ališauskas, Vytautas (Senoji Lietuvos literatūra, 2014)
Having discussed, more or less consistently (even if not quite exhaustively), the main transformations of the myth of the founding of Vilnius in the writings of the Grand Duchy of Lithuania, an attempt could be made to generalize this overview. We have tried to substantiate a hypothesis according to which the myth was created in Gediminas’ court. It should be related to the ruler’s desire to highlight the sacral aspect of the founding of a new capital and to confirm the legality of the new formation, which was to replace the old sacred site. It also reflects identity-consolidating values and aims of the dynamic ‘great pagan power’, which echoed those of Gediminas’ diplomatic activities. It is worth noting that the howl of the iron-clad wolf heralds the glory not of the monarch, but of his capital. The early modern period asks for a new relation with the myth. This relation is brought about by the context of Christianity and by the growing significance of rational thinking. A myth mutates when it loses the function of independent and universal narrative in various autonomous discourses. It becomes either a plausible story, or its opposite – a fairy-tale. Each of these forms reflect a new actual Sitz im Leben (‘setting in life’) and is applicable for the expression of new values. However, the Catholic and the Protestant contexts do not withdraw the aspiration of the myth to link the founding of the new capital with a sacral sanction. The specific pagan elements (e.g., the role of Lizdeika) being diminished, the assessment, from the Christian point of view, of religious legitimacy or validity of the ruler’s vision and its interpretation is eschewed. Stryjkowski’s and Kojalavičius’ historicized narratives link the fame of Vilnius with civic valour and with the transformation of the capital into a typical European city, which becomes a paradigmatic interpretation of the dream. A myth which becomes a fairy-tale and no longer claims the status of an authoritative narrative that shapes the integrity of a political community is labile, because not only its characters but also its central message can change according to the needs of the narrators and the addressees. Rhetoric adaptations of the myth reflect fragmentation of the public life and erosion of solid political values. An example of how, in the eighteenth century, the myth of the founding of Vilnius totally loses its authentic place in the hierarchy of narratives that unite the community is Grzybowski’s rhetoric deconstruction, which not only transforms the myth into a fairy-tale, but also imparts a contrary message to it. The topicality of the myth in the perspective of the Christian religion and rational thinking is eventually resolved by essential secularization of the narrative and by attributing the founding of the new capital to Gediminas’ political acumen. In this way the ruler’s figure as mythically legitimising and following the logic of the myth in its actions, is rejected.